If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 24b Solving 6 = 24b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-24b' to each side of the equation. 6 + -24b = 24b + -24b Combine like terms: 24b + -24b = 0 6 + -24b = 0 Add '-6' to each side of the equation. 6 + -6 + -24b = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -24b = 0 + -6 -24b = 0 + -6 Combine like terms: 0 + -6 = -6 -24b = -6 Divide each side by '-24'. b = 0.25 Simplifying b = 0.25
| (x-1)(x-1)+3=12 | | -170=10(x-8) | | 4-7+2r+8r= | | -294-110x+4x^2=450 | | w/9.6=3 | | 57=8p+9 | | 33=15x | | 0=4(x+3) | | 3x^2+6xy-9xy= | | (11x+3)2=16 | | -1+2b=-7 | | X-3/4x-5=1 | | 5a/11a | | 3(9+x)=45 | | 9x+3y-5=6x-9y+10 | | 4x^2+3=259 | | x^2(2x+3)(2x+3)=194 | | -6(3+b)=-126 | | 8m+4-9m= | | 8^1/3x16^3/4 | | 6x+2(x+3)=38 | | 8-8x=-48 | | 4x^2+12x-185=0 | | x^4-2x^3+3x^2-2x-3=0 | | 6b=90 | | y=11x^2-3x | | -96=16n | | 45*50*x=26250 | | (5.4)(-7.4)= | | 3=4+v | | -3=3+a | | 9(x+33)=324 |